Improving Visualization of Large Hierarchical Clustering - Gilles Bisson; Renaud Blanch (IV'12: Proceedings of the International Conference on Information Visualisation, 2012)
The classical representation of a binary tree generated by a hierarchical clustering is a node-link-based visualization denoted as a dendrogram. It allows users to explore in a simple way the clusters and the relationships between instances. However, exploration of large dendrograms is known to be difficult due to the graphical and cognitive information overload involved. Here, we discuss the current approaches and we introduce Stacked Trees, a new Focus+Context visualization technique that allows the exploration of the hierarchical clustering of up to fifty thousands nodes on a standard-sized screen.